The sensitivity of pan-TRK immunohistochemistry in solid tumours: A meta-analysis. (September 2022) - Hondelink, Liesbeth M.; Schrader, Anne M.R.; Asri Aghmuni, Golzar; Solleveld-Westerink, Nienke; Cleton-Jansen, Anne-Marie; van Egmond, Demi; Boot, Arnoud; Ouahoud, Sarah; Khalifa, Midia N.; Wai Lam, Suk; Morreau, Hans; Bovee, Judith V.M.G.; et al.
Abstract: Introduction: Since the approval of neurotrophic tropomyosin receptor kinase ( NTRK ) tyrosine kinase inhibitors for fist-line advanced stage pan-cancer therapy, pathologists and molecular biologists have been facing a complex question: how should the large volume of specimens be screened for NTRK fusions? Immunohistochemistry is fast and cheap, but the sensitivity compared to RNA NGS is unclear. Methods: We performed RNA-based next-generation sequencing on 1, 329 cases and stained 24 NTRK -rearranged cases immunohistochemically with pan-TRK (ERP17341). Additionally, we performed a meta-analysis of the literature. After screening 580 studies, 200 additional NTRK -rearranged cases from 13 studies, analysed with sensitive molecular diagnostics as well as pan-TRK IHC, were included. Results: In the included 224 NTRK-rearranged solid tumours, the sensitivity for pan-TRK IHC was 82% and the false-negative rate was 18%. NTRK3 fusions had more false negatives (27%) compared to NTRK1 (6%) and NTRK2 (14%) (p = 0.0006). Membranous, nuclear and peri-nuclear staining patterns strongly correlated with different fusion products, with membranous staining being more prevalent in NTRK1 and NTRK2, nuclear in NTRK3, and perinuclear in NTRK1 . Conclusion: Despite a reduction in the number of molecular analysis, using pan-TRK immunohistochemistry as a prescreening method to detect NTRK fusions in solid tumours will miss 18% of all NTRK -fused cases (especially involving NTRK3 ). Therefore, the most comprehensive and optimal option to detect NTRK fusions is to perform molecular testing on all eligible cases. However, in case of financial or logistical limitations, an immunohistochemistry-first approach is defensible in tumours with a low prevalence of NTRK fusions. Highlights: Neurotrophic tropomyosin receptor kinase ( NTRK ) inhibitors were recently accepted as first-line pan-tumour treatment. Laboratories worldwide are faced with the setup of an NTRK screening strategy. This meta-analysis includes 7000 cases of which 224 harbour NTRK fusions. Sensitivity of pan-TRK immunohistochemistry is 82%, missing 18% of NTRK fusions. NTRK screening should be performed with molecular methods, if possible.